Tumor Vasculature Targeted Photodynamic Therapy for Enhanced Delivery of Nanoparticles - Zhen, Zipeng (American Chemical Society, 2014)
[Image: see text] Delivery of nanoparticle drugs to tumors relies heavily on the enhanced permeability and retention (EPR) effect. While many consider the effect to be equally effective on all tumors, it varies drastically among the tumors’ origins, stages, and organs, owing much to differences in vessel leakiness. Suboptimal EPR effect represents a major problem in the translation of nanomedicine to the clinic. In the present study, we introduce a photodynamic therapy (PDT)-based EPR enhancement technology. The method uses RGD-modified ferritin (RFRT) as “smart” carriers that site-specifically deliver (1)O(2) to the tumor endothelium. The photodynamic stimulus can cause permeabilized tumor vessels that facilitate extravasation of nanoparticles at the sites. The method has proven to be safe, selective, and effective. Increased tumor uptake was observed with a wide range of nanoparticles by as much as 20.08-fold. It is expected that the methodology can find wide applications in the area of nanomedicine.